Long-term evolution and stability of Saturnian small satellites: Aegaeon, Methone, Anthe and Pallene - Muñoz-Gutiérrez, M. A. [UNESP]; Giuliatti Winter, S. [UNESP] (Oxford University Press (OUP), 2017)
Aegaeon, Methone, Anthe and Pallene are four Saturnian small moons, discovered by the Cassini spacecraft. Although their orbital characterization has been carried on by a number of authors, their long-term evolution has not been studied in detail so far. In this work, we numerically explore the long-term evolution, up to 105 yr, of the small moons in a system formed by an oblate Saturn and the five largest moons close to the region: Janus, Epimetheus, Mimas, Enceladus and Tethys. By using frequency analysis, we determined the stability of the small moons and characterize, through diffusion maps, the dynamical behaviour of a wide region of geometric phase space, a versus e, surrounding them. Those maps could shed light on the possible initial number of small bodies close to Mimas, and help to better understand the dynamical origin of the small satellites.We found that the four small moons are long-term stable and no mark of chaos is found for them. Aegaeon, Methone and Anthe could remain unaltered for at least~0.5Myr, given the current configuration of the system. They remain well trapped in the corotation eccentricity resonances with Mimas in which they currently librate. However, perturbations from nearby resonances, such as Lindblad eccentricity resonances with Mimas, seem responsible for largest variations observed for Methone and Anthe. Pallene remains in a non-resonant orbit and it is the more stable, at least for 64 Myr. Nonetheless, it is affected by a quasi-resonance with Mimas, which induces long-term orbital oscillations of its eccentricity and inclination.
Keywords: Methods: numerical; Planets and satellites: dynamical evolution and stability; Planets and satellites: rings